The Importance of Moving to International Financial Reporting Standards for Indonesian Companies - Andian Ari Istiningrum (Jurnal Pendidikan Akuntansi Indonesia, 2011)
The aim of this study is to determine basic differences between US GAAP and IFRSand provides some solutions to overcome problems that arise due to those differences.Literature review is used in this study to obtain the data about the effects of moving to IFRSin other countries. The results that are achieved in this study are: (i) transition to IFRS willchange financial position, financial performance, and cash flows of companies, (ii) benefitsthat companies take from transition to IFRS outweigh all costs that incur in the conversion,and (iii) IFRS 1 provides important guidance for a first time adopter.